Blue carbon development in China: realistic foundation, internal demands, and the construction of blue carbon market trading mode - Li, Ping; Liu, Dahai; Liu, Chao; Li, Xiaoxuan; Liu, Zhenhang; Zhu, Yanjing; Peng, Bo (Frontiers in Marine Science, 2024)
Promoting the inclusion of blue carbon in market trading is crucial for recognizing its value and protecting the marine ecological environment. However, China currently does not have an internationally influential blue carbon market trading platform, which hampers the transmission of supply and demand in the blue carbon market and prevents the realization of blue carbon value. In this study, we analyze the feasibility and necessity of establishing a trading mode for the blue carbon market in China. We examine the realistic basis and internal demands of China's blue carbon market to support our analysis. Secondly, the introduction of futures trading in the blue carbon market's trading mode allows for the use of futures pricing methods and multiple financial instruments to address the challenges of income cost mismatch and capital preservation and appreciation in blue carbon project development. The paper also discusses key strategies for the development of China's blue carbon market, including the creation of a blue carbon trading methodology, the improvement of preservation and appreciation mechanisms, and the establishment of a unified trading platform.These strategies aim to provide intellectual support and decision-making reference for the construction of the market.